Simultaneous Multi-Vessel Subacute Stent Thromboses in Zotarolimus-Eluting Stents - Kim, Yong-Hyun (The Korean Society of Cardiology, 2010)
Despite its low incidence, stent thrombosis (ST) is one of the most dreaded complications of percutaneous coronary intervention. Endeavor (Medtronics Europe SA) is a new zotarolimus-eluting stent (ZES) with a favorable safety profile that was reported in early and ongoing trials. However, few lethal stent thromboses related to this new drug eluting stent (DES) have been reported. We experienced a case of simultaneous subacute ZES thromboses, 6 days after stent implantations in the proximal left anterior descending artery and the proximal right coronary artery (RCA).